Akuntabilitas Kinerja ASN Berbasis Digitalisasi dalam Pelayanan Pangan Mendukung Asta Cita Deli Serdang - Saima Rambe; Ratna Sari Dewi; Rana Fathinah Ananda (Politeknik Ganesha Medan, 2026)
The performance accountability of State Civil Apparatus (ASN) is an important element in ensuring the quality of public services in the food sector and supporting the achievement of the national food security agenda. This study aims to analyze the effect of digital technology-based ASN performance accountability on public services in the food sector and its support for the Asta Cita of national food security in Deli Serdang Regency, as well as to examine the mediating role of public services in the food sector. The study used a quantitative approach with an explanatory design and cross-sectional data collection. The research sample consisted of 34 ASN directly involved in public services in the food sector and was selected using purposive sampling. Data were collected through a Likert-scale questionnaire and analyzed using Partial Least Squares-Structural Equation Modeling using SmartPLS. The results showed that ASN performance accountability had a positive and significant effect on supporting the achievement of Asta Cita of national food security with a path coefficient of 0.617 and p<0.001. ASN performance accountability also had a positive and significant effect on public services in the food sector with a coefficient of 0.729 and p<0.001. Public services in the food sector have the strongest positive and significant influence on support for the achievement of Asta Cita with a coefficient of 0.846 and p<0.001, and are also proven to mediate the relationship between ASN performance accountability and support for the achievement of Asta Cita. These findings imply the need for integration of accountability systems, digital reporting, data traceability, and improvement of ASN competencies. It is concluded that strengthening accountability based on digital technology can improve the quality of public services in the food sector and strengthen the implementation of food security policies. Future research is recommended to expand the study area, use a longitudinal design, and add variables of digital competency, internal supervision, institutional coordination, and community participation.